2006
DOI: 10.1590/s1677-55382006000500011
|View full text |Cite
|
Sign up to set email alerts
|

Small round blue cell tumor of seminal vesicle in a young patient

Abstract: Seminal vesicle tumor is a rare disease with unclear origin. Generally, it is presented as a pelvic mass that can be detected by sonography and digital rectal exam. The authors report a 25-year-old patient with a pelvic mass which the magnetic resonance and surgical specimen reveal a seminal vesicle tumor. Immunohistochemical findings favored a primitive neuroectodermal tumor of the seminal vesicle. Herein, the treatment, histological and histochemical findings of this entity are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…PNETs of seminal vesicle origin are extremely rare, with a few cases documented; in addition, they are more common in children and adolescents, making the age of our patient unusual [5]. The presentation of seminal vesicle PNETs can vary from an incidental finding during imaging to lower abdominal pain, and compressive symptoms such as voiding difficulties, dysuria, urinary frequency or constipation (Table 1) [1][2][3]4,6]. ( The primary localized seminal vesicle tumor is possibly curable; however, the secondary spread, mainly from the prostate, bladder, and rectum, is usually an advanced disease with poorer outcomes; therefore, differentiation between primary and secondary tumors is crucial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PNETs of seminal vesicle origin are extremely rare, with a few cases documented; in addition, they are more common in children and adolescents, making the age of our patient unusual [5]. The presentation of seminal vesicle PNETs can vary from an incidental finding during imaging to lower abdominal pain, and compressive symptoms such as voiding difficulties, dysuria, urinary frequency or constipation (Table 1) [1][2][3]4,6]. ( The primary localized seminal vesicle tumor is possibly curable; however, the secondary spread, mainly from the prostate, bladder, and rectum, is usually an advanced disease with poorer outcomes; therefore, differentiation between primary and secondary tumors is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…They can arise from either epithelial or mesenchymal cells, with carcinomas being the most prevalent [1]. Ewing's sarcoma of the prostate and seminal vesicle is exceedingly rare in adolescents and young adults representing less than 0.1% of all primary tumors [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies showed that needle biopsy findings compared to those of surgical and autopsy specimens may present a diagnostic challenge because benign characteristics on a histopathology exam does not rule out the absence of a carcinoma in a retrovesical mass. 12 Dahms et al 13 shown in a retrospective multi-institution study with 21 male patients the difficulty in diagnosis of retrovesical masses for eleven different diagnoses. Therefore, the lesion should be completely resected and RP should be considered if high-grade elements are identified.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Only two cases of PNET of seminal vesicle have been reported in the literature. [34] It is important to differentiate between primary and secondary spread as the former is a localized disease with possibility of cure while the later is usually an advanced disease with dismal prognosis.…”
Section: Disscusionmentioning
confidence: 99%